Self-assessed masticatory function and frailty in Brazilian older adults: the FIBRA Study - Clarice Santana Milagres; Luísa Helena do Nascimento Tôrres; Talita Bonato de Almeida; Anita Liberalesso Neri; José Leopoldo Ferreira Antunes; Maria da Luz Rosário de Sousa (Revista de Saúde Pública, 2022)
ABSTRACT OBJETIVE To investigate the relationship between the masticatory function and the frailty of older people. METHODS Exploratory cross-sectional study using secondary data from the FIBRA Project on the frailty conditions of older people living in urban areas of six Brazilian municipalities, from 2008 to 2009. The population consisted of older adults aged 65 and over with no cognitive impairment. A single session identification questionnaire and the Mini-Mental State Examination (MMSE) were applied, followed by collecting sociodemographic data and data on the participants’ self-assessment of masticatory function, general health, and oral health. RESULTS 2,341 older people (164 frail older adults), of whom 63.2% reported not having seen a dentist in the last year, and approximately 26% of them had three or more functional feeding problems. Older participants (OR = 2.88; 95%CI: 2.01–4.13), who are retired (OR = 2.31; 95%CI: 1.18–5.53), those who were depressed (OR = 2.31; 95%CI: 1.58–3.38), and those who self-assessed their general health as worse compared to others of the same age (OR = 3.91; 95%CI: 2.39–6.40) were at higher risk of frailty. Three or more problems related to the functional aspects of mastication were associated with a greater chance of frailty (OR = 2.06; 95%CI: 1.25–3.41). CONCLUSION This study found an association between masticatory function and a greater chance of frailty among the studied population.